Reeds Western almanac 2009 - Du Port, Andy; Featherstone, Neville (Adlard Coles Nautical, 2008)
The Reeds Western Almanac is ideal for any boater lucky enough to cruise and race in the superb waters off the coast of Western Scotland or Ireland. It offers ready access to essential navigation information by virtue of its clear layout and user friendly format.